The heart of change : real-life stories of how peple change their organizations - Kotter, John P., 1947-; Cohen, Dan S., ....- (Boston : Harvard Business Review Press, 2002)
The Heart of Change is John Kotter's follow-up to his enormously popular first book, Leading Change, in which he outlined a framework for implementing change that sidesteps many of the pitfalls common to organisations looking to turn themselves around. The essence of Kotter's message is this: the reason so many change initiatives fail is because they rely too much on "data gathering, analysis, report writing, and presentations" instead of a more creative approach aimed at grabbing the "feelings that motivate useful action". In The Heart of Change, Kotter, with the help of Dan Cohen, a partner at Deloitte Consulting, shows how his eight-step approach has worked at over 100 organisations. And in just about each case, change happened because the players were lead to "see" and "feel" the change. In one example, a sales representative underscores a sense of urgency to change a manufacturing process by showing a videotape interview of an unhappy customer; in another example, a purchasing manager makes his point to senior management about corporate waste by displaying on the company's boardroom table the 424 different kinds of gloves that the company had procured through different vendors at vastly different prices. Well written and loaded with real-life examples and practical advice The Heart of Change towers over other change management titles. Managers and employees at organisations both big and small will find much to draw from. --Harry C Edwards
Keywords: Herstructurering -- Organisaties